Testing a concurrent model of social anxiety in preadolescence. (November 2020) - Rapee, Ronald M.; Forbes, Miriam K.; Oar, Ella L.; Richardson, Cele E.; Johnco, Carly J.; Magson, Natasha R.; Fardouly, Jasmine
Social anxiety is a common mental disorder with an average age of onset in early adolescence. Current theories focus largely on risk factors that are present from early in life, but reasons for onset of the disorder as youth move into adolescence are rarely discussed. We recently proposed a model of the onset of certain mental disorders during the adolescent years based on characteristics of adolescent development. While this model will require longitudinal testing, the current article establishes concurrent associations between relevant variables in a cohort of 528 preadolescents ( M age = 11.2 years) at baseline. Youth with social anxiety disorder differed significantly from other youth on measures of social comparison (including physical appearance comparisons, self-rated attractiveness, and negative peer comparisons on social media) as well as positive peer connections (including self-reported school belonging, number of friends, victimization, and peer affiliation). A structural equation model showed that symptom levels of social anxiety were directly related to social comparisons and peer connections, as well as indirectly associated with pubertal development and social comparisons. This pattern was not moderated by sex of youth.